2021
DOI: 10.1007/s11845-021-02667-3
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary features of post-COVID-19 patients: muscle function, physical activity, mood, and sleep quality

Abstract: Background Coronavirus disease 2019 (COVID-19) represents a wide range of clinical manifestations, even if mild disease severity. It has been known that pulmonary function is affected by COVID-19 during infection and mid-to-long term. However, there is inadequate evidence about extrapulmonary features in post-COVID-19 patients. Aims This study aimed to investigate extrapulmonary features in post-COVID-19 patients who recovered from mild and moderate disease severity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 41 publications
2
64
4
1
Order By: Relevance
“…Unlike our study, which showed no significant differences in HGS between patients with PCS and controls, Tanriverdi et al. ( 2021 ) observed reduced HGS in 39.6% of the participants when they were evaluated 3 months after the diagnosis of COVID‐19. Comparing institutionalized older adults at two moments of the COVID‐19 pandemic, Greco et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike our study, which showed no significant differences in HGS between patients with PCS and controls, Tanriverdi et al. ( 2021 ) observed reduced HGS in 39.6% of the participants when they were evaluated 3 months after the diagnosis of COVID‐19. Comparing institutionalized older adults at two moments of the COVID‐19 pandemic, Greco et al.…”
Section: Discussioncontrasting
confidence: 99%
“…As far as muscle function is concerned, low handgrip strength (HGS), a proxy marker of muscle strength and a marker of sarcopenia, has been associated with all-cause and disease-specific mortality, future function, bone mineral density, fractures, cognition and depression, and hospitalization (13). In critical ICU COVID-19 patients, muscle wasting and decreased muscle strength occurred early and rapidly (14) and still persisted at 3 months from discharge (15); similar observations were also reported in patients who recovered from mild-to-moderate disease (16). Thus, in COVID-19 patients, muscle weakness, fatigue, and low exercise capacity may be related to poor muscle quality and low HGS (17), while a lower HGS is an independent risk factor for disease severity (18,19), longer hospitalization (20), and mortality (21).…”
Section: Introductionmentioning
confidence: 57%
“…As for muscle function, it is worth recalling that in critical ICU COVID-19 patients, muscle wasting and decreased muscle strength occurred early and rapidly ( 14) and persisted at 3 months from discharge (15), with similar observations also in mild-to-moderate disease (16). COVID-19 can accelerate the aging process of institutionalized older adults (17), while lower HGS is an independent risk factor for disease severity (18,19), hospital stay (20), and mortality (21).…”
Section: Discussionmentioning
confidence: 87%
“…Systemic CS such as dexamethasone (DX) and methylprednisolone (MPS) are frequently used in the treatment of hospitalised and critically ill COVID-19 patients to alleviate “cytokine storm” [ 13 ], and to reduce the need for mechanical ventilation, duration of hospitalisation, and mortality [ 9 11 ]. Furthermore, critically ill patients with severe COVID-19 may have an associated adrenal insufficiency which may require CS treatment [ 46 ]. Cano et al [ 10 ] reported that CS was administered in 51.3% of ICU patients, in 35.3% of mechanically ventilated patients, and in 40% with severe COVID-19.…”
Section: Corticosteroids In Covid-19 Treatmentmentioning
confidence: 99%